2018
DOI: 10.1002/qua.25796
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies on the formation of aza‐oxypentadienyl intermediates from alkylidene oxaziridines and keteneimine oxides and their conversion to 1,5‐dihydropyrrolones

Abstract: The rearrangements of alkylidene oxaziridines 1a,b (a, R = Me; b, R = OMe) and keteneimine oxides 1’a,b to 1,5‐dihydropyrrolones 3a,b have been computationally studied at the UM062X/Def2TZVPP(PCM,TFE)//UM062X/Def2SVP(PCM,TFE) level. The mechanism for conversion of 1a‐3a is predicted to be stepwise, with intermediacy of the acyclic aza‐oxypentadienyl species 4a. The stabilization provided by the nitrogen of the oxaziridine makes the ring opening of 1a to diradical/zwitterionic intermediates 4a more feasible tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Structure 2 b discussed above is a zwitterionic compound on the close‐shell singlet potential energy surfaces. As previous theoretical works indicated that azaoxyallyl cations may also be described as open‐shell singlet diradicals, [28] we attempted to locate such a spin state by using “guess=mix” in unrestricted DFT calculations. We have successfully optimized such a state of 2 b , which has the <S 2 > value of 0.398 and lies at 0.8 kcal/mol lower‐lying than the corresponding close‐shell singlet state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structure 2 b discussed above is a zwitterionic compound on the close‐shell singlet potential energy surfaces. As previous theoretical works indicated that azaoxyallyl cations may also be described as open‐shell singlet diradicals, [28] we attempted to locate such a spin state by using “guess=mix” in unrestricted DFT calculations. We have successfully optimized such a state of 2 b , which has the <S 2 > value of 0.398 and lies at 0.8 kcal/mol lower‐lying than the corresponding close‐shell singlet state.…”
Section: Resultsmentioning
confidence: 99%
“…Although several computational studied on the structures and reactivity of azaoxyallyl cations have been available in the literature, [27,28] detailed mechanistic analyses on the [3+2] cycloaddition with a carbonyl group and comparison of different cycloaddition pathways have been lacking. This work will present a series of density functional theory (DFT) calculations on the mechanism of the cycloaddition reactions given in Scheme 2 to address the above issues.…”
Section: Introductionmentioning
confidence: 99%